Bioassay-Guided Fractionation, ESI-MS Scan, Phytochemical Screening, and Antiplasmodial Activity of Afzelia africana - Bright Yaw Vigbedor; Jonathan Osei-Owusu; Ralph Kwakye; David Neglo (Biochemistry Research International)
Background. Afzelia africana is a plant species with reported numerous medicinal potentials and secondary metabolites. Various parts of the plant have been applied for the treatment of hernia, rheumatism, pain, lumbago, malaria, etc. The study seeks to evaluate the phytochemical constituents, antiplasmodial, and ESI-MS scan of bioassay-guided fractions from the methanol extract of the bark of the plant. Aims. The main aim of the study was to carry out bioassay-guided fractionation of the crude methanol extract of Afzelia africana in order to isolate fractions and to evaluate their antiplasmodial activities and ESI-MS fingerprints. Methods. The methods employed include column chromatographic fractionation, phytochemical screening, antiplasmodial activity (malaria SYBER green assay (MSF)), and ESI-MS profile (full ESI-MS scan). Results. The column chromatographic fractionation and phytochemical screening of the plant led to the separation of the following four fractions: 1 (flavonoids, phenolics, glycosides, terpenoids, and steroids), 2 (alkaloids, anthraquinones, flavonoids, phenolics, glycosides, terpenoids, and steroids), 3 (anthraquinones, flavonoids, phenolics, glycosides, terpenoids, and steroids), and 4 (alkaloids, flavonoids, phenolics, glycosides, terpenoids, and steroids). The antiplasmodial activities of the fractions were tested against the 3D7 strain of Plasmodium falciparum with reported stronger activities for 1 (IC50: 0.097 ± 0.034 μg/mL) and 3 (IC50: 1.43 ± 0.072 μg/mL), and weaker activities for 2 (IC50: >100 μg/mL) and 4 (IC50: 37.09 ± 6.14 μg/mL). The full ESI-MS fingerprint of fractions 1, 2, 3, and 4 revealed the presence of 14, 24, 34, and 37 major molecular ions or compounds in each fraction, respectively.